KENYA: Hekima at 40, Celebrating Decades of Women’s Theological Empowerment - Opondo, Jacinta Auma (2023)
Founded in 1984 as a Jesuit School of Theology to a few students of the Society of Jesus (Jesuits), Hekima University College (HUC) has advanced its mission as a centre for excellent formation, research and intellectual scholarship committed to offering a high-quality, integral, and contextualized education to include students from about fourteen local and international religious congregations. As part of the celebrations marking the 40th anniversary of the Jesuit institution, Sr Dr Jacinta Opondo, a member of the Franciscan Sisters of St. Anna (FSSA) and a faculty member at HUC Jesuit School of Theology writes about the noble mission of HUC in providing opportunities to religious women to study theology for a stronger foundation for ministry, personal enrichment and greater capacity for leadership.
free